Inventory, diversity and communities of macrofungi in the Collestrada forest (Umbria, central Italy). (2nd September 2016) - Angelini, P.; Bistocchi, G.; Arcangeli, A.; Rubini, A.; Venanzoni, R.
Abstract: In this study, an inventory of the macrofungi in the Collestrada forest (Umbria, Italy).was performed through the collection of sporocarps of basidiomycetes and ascomycetes over a period of three years. Sampling was performed in selected sites' representatives of the seven wood types present in the Collestrada forest. A total of 341 species were identified and a comprehensive spatial and seasonal analysis of macrofungal species richness, abundance and diversity was performed. Patterns of fungal fructification varied greatly between species and ecological groups, over the years and seasons. Differences in fungal species composition and abundance were detected between the wood types, however, changes of meteorogical conditions, especially the rainfall level and relative humidity, during the growing seasons and years have a major impact on determining the structure of fungal communities. As 143 of the fungal species identified matched with those included in the Red List (or proposals for Red Lists) in several European countries, the studied sites may represent important areas for conservation of fungal diversity (IFA). The results of this study constitute a powerful tool to optimize conservation strategies and policy.